2022
DOI: 10.1139/cjb-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Why is the rainforest lichen Methuselah’s beard (Usnea longissima) so rare in British Columbia’s inland temperate rainforest?

Abstract: Coastal (CTR) and inland temperate rainforests (ITR) in western North America share a rich oceanic lichen flora. The distinctive Methuselah’s beard lichen (Usnea longissima) is an exception to this pattern of shared distributions, with very few ITR locations. Does this absence reflect dispersal limitations or climatic intolerance? To answer this question, we transplanted U. longissima thalli from the CTR to three ITR locations, assessing growth rates against reciprocal CTR transplants. Canopy microclimate meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Both niche specialism and dispersal limitation (Williams and Ellis, 2018) contribute to its strong preference for humid old-growth boreal forests with long continuity of canopy cover. Despite high growth capacity (Gauslaa et al, 2007;Keon and Muir, 2002;Strother et al, 2022), the high degree of niche specialism and dispersal limitation suggest that the lichen has limited capacity to shift its vertical and horizontal distribution in response to changes in canopy structure and climate. The development of populations is driven by a small number of 'source trees' with large populations occurring at higher vertical positions, while 'sink trees' with small populations close to ground are less important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both niche specialism and dispersal limitation (Williams and Ellis, 2018) contribute to its strong preference for humid old-growth boreal forests with long continuity of canopy cover. Despite high growth capacity (Gauslaa et al, 2007;Keon and Muir, 2002;Strother et al, 2022), the high degree of niche specialism and dispersal limitation suggest that the lichen has limited capacity to shift its vertical and horizontal distribution in response to changes in canopy structure and climate. The development of populations is driven by a small number of 'source trees' with large populations occurring at higher vertical positions, while 'sink trees' with small populations close to ground are less important.…”
Section: Discussionmentioning
confidence: 99%
“…They have low probability of being transported over longer distances than a few m's from the source trees, consistent with the clustering of host trees. Transplant studies suggest that dispersal limitations are important in determining the distribution of U. longissima (Keon and Muir, 2002;Strother et al, 2022) and other old-growth forest lichens (Sillett et al, 2000;Scheidegger and Werth, 2009).…”
Section: Horizontal Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a wider habitat range observed (e.g., more phorophyte species occupied; Table 1 ) may partly result from local population size (for any reason) when habitats differ in their quality. Investigation of such patterns is expectably difficult in the case of delayed, hidden, and cumulative impacts of past events, such as recovery from disturbance, or a history of repeated exposure to contaminants [ 129 , 130 ]. An important study on epilithic lichens found that their colonization rate of habitat patches is related to both the local abundance and range size [ 131 ].…”
Section: Causal Mechanisms: Ecophysiology and Demographic Processesmentioning
confidence: 99%